CGIAR annual conference - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
A significant budgetary cutback was adopted at the Consultative Group on International Agricultural Research's (CGIAR) annual conference in Washington held from 28 October -1 November 1991. 1992 will see the budget of $251 million cut by six...